Penerapan Business Process Model and Notation dalam Meningkatkan Efisiensi Proses Bisnis Aplikasi PLN Mobile - Yan Pandra; Imamulhakim Syahid Putra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to improve business process efficiency in the PLN Mobile application through the implementation of Business Process Model and Notation (BPMN). PLN Mobile is a digital innovation by PT PLN (Persero) that allows customers to access services such as bill payment, outage reporting, and service requests. However, various challenges remain, including slow processing times, lack of system integration, and inefficient workflows. The research was conducted at PT PLN (Persero) UP2D S2JB using observation, interviews, and literature review. The results indicate that modeling business processes using BPMN effectively maps workflows, identifies bottlenecks, and offers digital-based solutions. The application of BPMN has been shown to increase transparency, reduce input errors, and accelerate customer service processes. This study recommends ongoing optimization through enhanced analytics features, system security, and regular training for operational staff.